Impact Analysis of Business Logic Refactoring from Client-Side to Server-Side on Application Performance in Distribution Management System at PT.XYZ - Susi Maria Purba; Frank Niroy Siahaan; Genesis Tombak Dapot Tua Panjaitan; Jopel Simarmata; Oloan Bonar Nainggolan (Sean Institute, 2026)
Although implementing client-side business logic remains a common practice in mobile application development, it can introduce significant performance inefficiencies. This study analyzes the performance impact of refactoring business logic from the client-side (Flutter) to the server-side (ASP.NET Web API) in the Delete feature of the Delivery List module within a Distribution Management System (DMS) deployed at PT. XYZ. Before refactoring, the Flutter client executed N sequential API calls per operation—one call per selected item. After refactoring, all selected items are sent in a single unified API call, with the server handling all internal iteration and routing logic. Performance evaluations were conducted programmatically using code implementations within Flutter across three key metrics: total execution time, memory usage, and network payload size. Testing was performed over 10 iterations in a controlled local environment. Results demonstrate that the server-side approach decreases average execution time by approximately 17.7%, mitigates extreme memory spikes by reducing peak memory consumption by 29.3%, and shrinks the network payload size by 0.76%. This study provides quantitative evidence that migrating business logic to the server-side yields measurable and significant performance improvements in Flutter-based mobile applications.